O impacto dos Benefícios Fiscais na tributação das empresas - Guimarães, Bruna Oliveira (2022)
The main objective of this dissertation is to understand the impact of tax benefits on corporate taxation, analyzing the tax benefits used by four companies when calculating the income tax for the period, in order to quantify the tax savings obtained by these companies, derived from the use of tax benefits. The tax benefits are mainly foreseen in the statute of tax benefits and in the investment tax code. For this reason, the literature review of this dissertation generically addresses the statute of fiscal benefits, as well as the investment tax code, presenting in detail some of the tax benefits that are included in this code. Regarding the practical component of this dissertation, we proceeded to analyze the tax benefits used by four companies, in the 2018, 2019, 2020 and 2021 tax periods, based on the Model 22 income statements for each year. Throughout this analysis, the formalisms presented in the literature review were highlighted, finally calculating the tax savings obtained by each company, through the comparison between the estimated tax with the influence of tax benefits and the calculation of the tax that would be estimated without the enjoyment of any tax benefits. The results achieved by the empirical study showed a strong impact of tax benefits on the estimated tax, which in turn results in a lower tax, thus influencing the net result for the period, since it is significantly higher when companies enjoy tax benefits.